2021
DOI: 10.1038/s10038-021-00930-0
|View full text |Cite
|
Sign up to set email alerts
|

Modeling colorectal cancer evolution

Abstract: Understanding cancer evolution provides a clue to tackle therapeutic difficulties in colorectal cancer. In this review, together with related works, we will introduce a series of our studies, in which we constructed an evolutionary model of colorectal cancer by combining genomic analysis and mathematical modeling. In our model, multiple subclones were generated by driver mutation acquisition and subsequent clonal expansion in early-stage tumors. Among the subclones, the one obtaining driver copy number alterat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 53 publications
0
9
0
1
Order By: Relevance
“…Most tumor clones from naive patients are wild strains, but some mutant clones (with drug-resistant clones) will emerge under drug pressure, which is a dynamic process. If a patient stops first-line regimen treatment for some time, the tumor clones may return to the original wild-type and become re-sensitized to the primary therapy ( 16 , 17 ). This dynamic tumor clonal evolution has been confirmed in other solid tumors.…”
Section: Discussion Of Therapeutic Strategies Of Anti-her2 Drugs Base...mentioning
confidence: 99%
“…Most tumor clones from naive patients are wild strains, but some mutant clones (with drug-resistant clones) will emerge under drug pressure, which is a dynamic process. If a patient stops first-line regimen treatment for some time, the tumor clones may return to the original wild-type and become re-sensitized to the primary therapy ( 16 , 17 ). This dynamic tumor clonal evolution has been confirmed in other solid tumors.…”
Section: Discussion Of Therapeutic Strategies Of Anti-her2 Drugs Base...mentioning
confidence: 99%
“…Understanding this heterogeneity and why tumors are heterogenous is crucial to understand how cancer initiates and evolves, how cancer can be attacked and at the same time how cancer can become resistant to therapy. This heterogeneity may be explained by a branching evolutionary process driven by genetic variation (mainly fostered by genomic instability) and natural selection of the fittest variant driven by microenvironment conditions or external pressures such as therapy ( Amirouchene-Angelozzi et al, 2017 ; Niida et al, 2021 ). The Darwinian principles of evolution and survival are the basis of tumor heterogeneity and clonal evolution, since the acquisition of different genetic and/or epigenetic alterations endows the tumor with greater survival capabilities, and the capacity to escape drug inhibition ( Kreso et al, 2013 ; Amirouchene-Angelozzi et al, 2017 ).…”
Section: Acquired Resistance To Anti-egfr Moab In Mcrc: Heterogeneity...mentioning
confidence: 99%
“…Evolutionary modelling is vital to enhance our understanding of tumour progression and to predict the prognostic value of cancer treatment, particularly targeted therapy [91]. Niida et al (2021) recently reported that using a combination of genomic analysis and mathematical modelling enabled better visualisation of cancer evolution, thus providing a better understanding of carcinogenesis and possible therapy [111]. They proposed that for CRC evolution, driver mutation and subsequent clonal expansion generate multiple clones in early-stage tumours.…”
Section: Analyses Of Crc Evolution and Heterogeneitymentioning
confidence: 99%